2022
DOI: 10.33423/jaf.v22i4.5342
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Critical Success Factors and Accounting Standard Codification Topic 606 Implementation Dynamics: A Correlational Study

Abstract: This study examined implementation critical success factors and ASC 606 implementation dynamics. The study includes organizational dynamics that strengthen change: responsiveness, absorptive capability, and organizational implementation context. The study investigated relationships between implementation critical success factors (CSF) and ASC 606 implementation outcomes to understand mechanisms most likely to cause a change in implementation outcomes. The study adopted the ex post facto nonexperimental correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This includes developing new methods for tracking and reporting virtual assets, as well as new standards for evaluating the value of these assets for financial reporting purposes. It is important to reconcile these virtual transactions with traditional financial reporting systems and ensure accounting methods are incorporated into an inclusive and broader financial reporting framework (Tafon et al , 2022). As standardised regulations for accounting and taxation in the metaverse are yet to be established (Deloitte, 2022b), the paper recommends that a case-based approach is advisable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes developing new methods for tracking and reporting virtual assets, as well as new standards for evaluating the value of these assets for financial reporting purposes. It is important to reconcile these virtual transactions with traditional financial reporting systems and ensure accounting methods are incorporated into an inclusive and broader financial reporting framework (Tafon et al , 2022). As standardised regulations for accounting and taxation in the metaverse are yet to be established (Deloitte, 2022b), the paper recommends that a case-based approach is advisable.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, comparing and reconciling the values may also be difficult as the values are reported differently by various organisations, leading to inconsistencies in financial reporting (Tafon et al , 2022). Because these are not physical goods, the determination of a fair value and point of transfer (when the user obtains control of the asset) will be a challenge as it is a key factor in recognising revenue as per accounting standards.…”
Section: Accounting Concerns In the Metaversementioning
confidence: 99%
“…In the metaverse, it is not easy to account for income, even if there are standards for some activities (The Accounting Standards Codification (ASC) 606) [21]. Tafon et al [22], analyzing the critical success factors of the implementation of The Accounting Standards Codification (ASC) 606, observed that organizations report the values of virtual assets differently, which complicates actual values but also the moment when the user obtains control over the asset. These particularities generated by virtual transactions represent a challenge for accounting that requires adapting accounting standards.…”
Section: The Perceived Utility Of the Metaverse By The Accounting Com...mentioning
confidence: 99%